Analysis of Saving Behavior and Locus of Control as a Mediating Variable of Generation Z in Mojokerto City - Syanita Lailatussaadah Syaifudin; Dhani Ichsanuddin Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Saving behavior is an important aspect of individual financial management that can affect long-term financial stability. The purpose of this study is to understand the factors that play a role in shaping saving behavior and its implications for the financial well-being of individuals, especially Generation Z in Mojokerto City. Using quantitative methods with primary data from the distribution of questionnaires. The number of samples was 100 Generation Z people in Mojokerto City determined by purposive sampling technique. The Structural Equation Model (SEM) technique was used in analyzing the data of this study with the help of SmartPLS software version 4.0. The results of the study explain that lifestyle variables can contribute to saving behavior, income cannot contribute to the saving behavior of Generation Z Mojokerto City and locus of control can also contribute to the saving behavior of Generation Z Mojokerto City. Locus of control is able to become a mediating variable in the relationship between lifestyle and income on the saving behavior of Generation Z Mojokerto City.